Exploring the migration of Muslims, Hindus and Sikhs in Birmingham by ward concentration and deprivation - Hussain, Serena (Migration Letters, 2021)
This paper explores the migration within as well as migration to Birmingham of Muslims, Hindus and Sikhs. It provides analysis and reflection on the relationship between migration, faith group concentration and deprivation. The findings demonstrate how Muslim, Hindu and Sikh migration trends differ for specific wards characterised by contrasting levels of both socio-economic disadvantage and faith group clustering. Hindus are shown to migrate to more affluent areas, however this does not necessarily translate to moving away from wards where there are clusters of the same faith group, as discussion on Hall Green illustrates. Muslims, on the other hand, displayed a greater propensity to move away from wards with high concentrations of the same faith group, yet this did not also result in moving to more affluent wards.